Plasma‐Assisted Fabrication of Fe2O3Co3O4 Nanomaterials as Anodes for Photoelectrochemical Water Splitting. Issue 1 (11th August 2015) - Carraro, Giorgio; Maccato, Chiara; Gasparotto, Alberto; Kaunisto, Kimmo; Sada, Cinzia; Barreca, Davide
Abstract : Nanocomposite Fe2 O3 Co3 O4 photoanodes for photoelectrochemical H2 O splitting were prepared by a plasma‐assisted route. Specifically, Fe2 O3 nanostructures were grown by plasma enhanced‐chemical vapor deposition, followed by cobalt sputtering for different process durations. The systems were annealed in air after, or both prior and after, sputtering of Co, to analyze the treatment influence on functional performances. The interplay between processing conditions and chemico‐physical features was investigated by a multi‐technique characterization. Photocurrent density measurements in sunlight‐assisted H2 O splitting revealed a performance improvement upon Co3 O4 loading. A cathodic shift of the onset potential was also observed, highlighting Co3 O4 activity as catalyst for the oxygen evolution reaction. Abstract : Fe2 O3 Co3 O4 nanomaterials are fabricated on FTO substrates by means of a two‐step strategy, consisting in the plasma enhanced‐CVD of Fe2 O3 followed by cobalt sputtering. A thorough characterization of the obtained systems as a function of thermal treatment conditions and cobalt loading is presented, followed by functional testing in photoelectrochemical water splitting activated by solar light.